The formation of a successful personality of a pupil in Ukrainian primary school during media education implementation - Hryhorii V. Tereshchuk; Iryna I. Kuzma; Oleksandra I. Yankovych; Halina I. Falfushynska (Academy of Cognitive and Natural Sciences, 2019)
The article substantiates the relevance of implementing the technology of formation of a successful personality of a primary school age pupil during media education implementation at primary school. A technology model is developed. The necessity of solving problems of success simultaneously with increasing the level of media culture of a pupil, the formation of key competencies for life, preparation of a child for the life's self-realization on the basis of the partnership implementation of schoolchildren, parents and teachers is proved. The need of the embodiment of the pedagogy of heart and the pedagogy of success is shown. The diagnostic toolkit for determining the levels of formation of the successful personality of primary school pupils is specified. The effective forms and methods of the schoolchildren education are substantiated: the creation of electronic books, projects "Rules of Success Achievement", "Stories of Success", watching movies about successful people with special needs, analysis of media products on the topic of success. The ways of educating parents about the problems of children's success are determined. The results of experimental research are analyzed. The necessity of improving the content of textbooks in the context of achieving success, increasing interest to children's periodicals is revealed. The formation of a successful pupil is considered as one of the ways to strengthen the Ukrainian state. The necessity of raising the authority of the teaching profession is proved.